(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the effects of different levels of camu-u fruit (Myrciaria dubia) flour in diets on zootechnical performance, body composition and physiological and histological responses of juvenile tilpia. It was used 500 juvenile tilapia, distributed in 20 tanks (1000L), in a completely randomized design with four treatments and five replications, fed three times a day until apparent satiation, for 48 days, with diets containing increasing levels of camu flour. -camu (0, 10, 20 and 30%). The increase in the inclusion of camu-camu in the diet resulted in a reduction in final weight, total length and specific growth rate, and an increase in apparent feed conversion, reduction in total and daily weight gain, fillet yield and carcass yield with and without head. Fish survival was not affected. Higher final weight, total length, file yield and specific growth rate obtained for fish fed a diet without camu-camu. The result is increased crude protein and lower body ether extract content. There was an increase in blood glucose concentration. There were no differences in the length, relationship between length and length and area of the villi of juveniles. For the length of the intestinal villi was statistically significant differences (P<0.05). It is concluded that camu improved the body composition of the fingerlings, the well-being of the fish and, despite not being able to survive, it improved the productive performance of juvenile Nile tilapia. New studies can be done with levels from 0 to 10%.